Conceptualization of the existential-system model of reorganization of the “worldview” of the personality: the introduction of ontological dominants - Svitlana Mykolaivna Kalishchuk (Insight: the psychological dimensions of society, 2020)
Purpose. The article highlights the successive steps of conceptualization of trans-theoretical existential-system approach to the reorganization of the semantic architectonics of personality consciousness. Methods. Spectral, structural and semiotic approaches provided a comprehensive methodological analysis of the procedural action of the existential-system concept. Results. An ontological field of the semantic model of the world of personality has been constructed. Five projections of the study of the personality have been revealed. The key concepts of theoretical design of the concept have been defined: “world”, “consciousness”, “worldview”, “meaning”, “system”, “semantic architectonics of consciousness”, “representations-experiences-thoughts”, “reorganization”, “self-attribution”. They describe the inner space of the psychological system of the existential-system concept, which is operated by a psychologist-specialist. A visual model of the theoretical construct of the existential-system approach has been constructed. It reflects the client’s representations. A meaningful scheme of interrelationships and interactions of ontological representations of eight perspectives of “correlation with the world” as an action of finding meaning has been offered. Diagnostic approaches’ complementarity has been substantiated. The connection scheme of elements of diagnostic-correctional approaches of existential-system concept of reorganization of the individual “worldview” has been offered: existential, system modeling and psychodrama, projective, psychosemantic, body-dynamic and transpersonal. The technical methods that objectively outline the methodological potential of the existential-system concept have been listed. Conclusions. The unity of diagnostic and corrective actions of the concept, which is provided by their internal phenomenology, has been substantiated. It has been proved that the focus and mechanism of reorganization of the existential-system concept is finding paradoxical meanings and paradoxical confrontation with oneself, with self-identity and the world that the client created for himself. It is determined that the existential-system concept is a trans-theoretical psychological system of providing the process of semantic dynamics of personality consciousness. Its goal is the maximum living and “fulfillment” of a life with authentic attitudes, freedom and responsibility for existence and the world.